ANALYSIS OF THE STATE OF THE PROBLEM OF PREPARATION OF TEACHERS OF NATURAL AND MATHEMATICAL SUBJECTS FOR WORK IN THE SCIENTIFIC LYCEUM - Marienko , М.В. (Journal of Information Technologies in Education (ITE), 2020)
The article presents an analysis of the results of the ascertaining stage of the pedagogical experiment "Designing a cloud-oriented methodological system of training teachers of natural and mathematical subjects to work in a scientific lyceum." An analysis of recent research and publications has shown that scholars have sufficiently considered the problem of reforming teacher training courses. A separate issue is revealed in Ukrainian research on the design of cloud-based systems, but the proposed systems relate exclusively to certain specialties, or are entirely scientific. Currently, there is no cloud-based system that would become a tool in the further preparation of teachers of science and mathematics to work in the scientific lyceum. The following were selected as experimental sites: Rivne Regional Institute of Postgraduate Pedagogical Education (2019, number of respondents - 45) and Zhytomyr Polytechnic State University (2020, number of respondents - 824). The current state of use of services by teachers of natural and mathematical subjects during the preparation of educational materials was clarified; the readiness of teachers to perform personally and teach students to conduct research work is analyzed and the state of awareness of teachers about the functions and requirements of scientific lyceums is determined. The analysis of the survey showed that most teachers recognize the need for a teacher of a scientific lyceum in scientific activities. Most respondents do not use English-language resources and services due to their low level of language proficiency. It has been found that one of the most important ways to get involved in science, according to math teachers, is to participate in scientific conferences. Regarding the implementation and use of the obtained research results, teachers plan to choose the following ways: publication of methodological materials and self-implementation. The analysis of the results of the survey of educators showed that among the respondents 574 people (69.7%) prefer to use information and communication technologies on a local computer. Analysis of the results of the ascertaining stage of the pedagogical experiment shows that there is a problem of preparing teachers of natural sciences and mathematics to work in the scientific lyceum, which needs further solution through preliminary testing and implementation of a specially created cloud-based methodological system